Scale and structure dependent solute diffusivity within microporous tissue engineering scaffolds - Offeddu, Giovanni S. (J Mater Sci Mater Med, 2020)
Diffusion of nutrients to cells cultured within three-dimensional scaffolds is fundamental for cell survival during development of the tissue construct, when no vasculature is present to aid transport. Significant efforts have been made to characterize the effect of structure on solute diffusivity in nanoporous hydrogels, yet a similar thorough characterization has not been attempted for microporous scaffolds. Here, we make use of freeze-dried collagen scaffolds, possessing pore sizes in the range 150–250 μm and isotropic or aligned morphology, to study the diffusivity of fluorescent dextran molecules. Fluorescence recovery after photobleaching is used to measure the self diffusivity of the solutes within single pores, while Fickian diffusion over scales larger than the pore size is studied by assessing the solute concentration profile within the materials over time. We show that, not only do the morphological parameters of the scaffolds significantly affect the diffusivity of the solutes, but also that the assessment of such diffusivity depends on the length scale of diffusion of the molecules under investigation, with the resulting diffusion coefficients being differently affected by the scaffold structure. The results provided can guide the design of scaffolds with tailored diffusivity and nutrient concentration profiles. [Image: see text]